Transcriptome and metabolome analyses reveal that Bacillus subtilis BS-Z15 lipopeptides mycosubtilin homologue mediates plant defense responses - Yang, Qilin; Zhang, Hui; You, Jia; Yang, Jun; Zhang, Qi; Zhao, Jinjin; Aimaier, Reyihanguli; Zhang, Jingbo; Han, Shengcheng; Zhao, Heping; Zhao, Huixin (Frontiers in Plant Science, 2023)
Microbial-plant interactions protect plants from external stimuli, releasing various elicitor that activate the plants defense response and regulate its growth. Bacillus subtilis BS-Z15 was screened from cotton inter-rhizosphere soil, antagonized various plant pathogens, and protected cotton against Verticillium dahliae. This study showed that the BS-Z15 lipopeptide mycosubtilin homologue could act as an elicitor to induce systemic resistance (ISR) in plants. Mycosubtilin homologue induced ROS burst and deposition, callose deposition, MAPK cascade phosphorylation, and up-regulated PR1 and PDF1.2 gene expression in Arabidopsis seedlings, moreover enhanced resistance of Arabidopsis to Pseudomonas syringae pv. Tomato DC3000 (Pst DC3000) and V. dahliae. Transcriptome analysis was then used to evaluate the impact of mycosubtilin homologue on plant gene expression control. Mycosubtilin homologues activated Arabidopsis ISR on genes in metabolic pathways such as Arabidopsis plant-pathogen interactions, phenylpropanoid biosynthesis, MAPK signaling pathway, and phytohormone signaling. These analyses revealed that mycosubtilin homologues mediate the regulation of plant systemic resistance and growth and development by affecting related metabolites in glycolysis and gluconeogenesis, pentose phosphate pathway, tricarboxylic acid cycle, and amino acid metabolism in Arabidopsis. These findings confirmed that a mycosubtilin homologue could trigger the initiation of the Arabidopsis ISR by interacting with a variety of PTI components and transcriptional metabolic signaling pathways.